INVENTARISASI JENIS-JENIS TANAMAN HIAS INTRODUKSI DI DESA PENGLIPURAN, KABUPATEN BANGLI, BALI - Zuraida, Ayu; Raka Dalem, A.A. Gde; Joni, Martin (SIMBIOSIS, 2018)
Panglipuran Village is one of the traditional villages in Bali that still prioritizes harmonization and sense of togetherness. The village is located in Kelurahan Kubu, Kecamatan Bangli, Bangli District, Bali. Panglipuran Village has many types of plants. The varieties of plants can be influenced by several factors: one of them is introduction. This research is conducted to examine the introduction of decorative plants in Panglipuran Village, with the purpose of providing information to villagers about those plants, so that their potential can be utilized in other travel destinations, especially the ones in Bali. The method used in this research is purposive sampling. Data were obtained through direct field observation and interviews with local villagers, and later were identified at Laboratorium Taksonomi Tumbuhan FMIPA, Udayana University. According to the results of this research, 32 types of introduction plants which comes from 24 different famili was found. Introduction of decorative plants in Panglipuran Village can be classified into 3 groups, which are 22 types of decorative flower plants, 8 types of decorative leaf plants, and a single type of decorative stem plants. Keywords : inventorisation, Panglipuran Village , decorative plants, introduction